PENYELENGGARAAN FUNGSI TERMINAL BARANG OLEH DINAS PERHUBUNGAN KOTA DUMAI TAHUN 2019 - Karmilia Arya Putri Kirana; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The implementation of the Dumai City Transportation Service goods terminal function as a road transportation infrastructure for the purposes of unloading and loading goods solves problems due to the circulation and movement of goods transport as well as intra and/or inter-modal movements of transportation. Everyone has needs that must be met but these needs cannot be met directly. Fulfillment of these needs must go through the process of logistics activities, namely planning, organizing, and controlling the flow of materials and services from suppliers to final users. In order to support these activities, road transport traffic must be created that is safe, comfortable, orderly, organized and efficient. The purpose of this study is to find out the Implementation of the Goods Terminal Function by the Dumai City Transportation Service in 2019 using a qualitative approach with a descriptive method. The research location is at the Dumai City Transportation Service. In collecting data, the writer uses interview and documentation techniques. The results of the study explain that in the Implementation of the Dumai City Transportation Service Goods Terminal, directly or indirectly it has an effect on people's lives individually and in groups. The positive effects that can be felt by the community are more orderly traffic around cross roads, and reduced damage on cross roads . However, the negative effect that is felt by the community is that the community is disturbed by the large amount of palm shell waste scattered on the streets. This disrupts traffic, especially those using motorbikes. Keywords: Local Government, Institutional, Implementation